Decorative wooden balusters on a balcony in Tromsø, Norway ... - Campbell, Sandy (University of Alberta Library, 2024)
Many houses in Tromsø have balconies to take advantage of the views. This one has decorative diamond and dagger cut wooden balusters. This balcony is painted white. ...